Principles of IP-Court Activity in Ukraine - S. V. Volovyk (Bulletin of Kharkiv National University of Internal Affairs)
The principles of IP-court activity in Ukraine have been studied. It has been emphasized that the urgent issues currently are to review the existing approaches to reforming the judicial system of Ukraine, based on the gained experience of establishing specialized courts, defining principles as guidelines for the functioning of IP-court in Ukraine as the Higher Specialized Judicial System of Ukraine.